Assessment of multiple factors affecting intelligence quotient of children of rural and urban areas of Rajasthan, India - Singhvi, Shreyans D.; Singh, Preksha T.; Bhandari, Gautam (International Journal of Research in Medical Sciences, 2020)
Background: Children are the future of our country and hence their mental and physical wellbeing should be our upmost priority. Undernutrition is a major public health problem in our country and is one of the most common reasons for morbidity and mortality in children under 5yrs of age. The first few years of life are particularly important because vital development occurs in all domains. Therefore, this study has aimed to study the Intelligence Quotient (IQ) of the children of the age group 3-5 in urban and rural areas and study the factors associated with it. Methods: A cross section study of the children group of population was performed. Two sections of the children group were taken for the study- children population residing in an urban area and children population residing in a rural community of Rajasthan, India. The data was compiled and analyzed using appropriate statistical methods. Results: In our study, we have found that The following chosen demographic factors were found associated with children Intelligence quotient (IQ) - nutritional status, socioeconomic status, and age, while gender was not found to be associated with IQ. Conclusions: As, cognitive development is fairly important to children and their future, it should be paid more acknowledgment, as well as early preventive methods of it’s associated factors.